The Wayward Dog: Is the Australian native dog or Dingo a distinct species? - Jackson, Stephen M.; Groves, Colin P.; Fleming, Peter J.s.; Aplin, Ken P.; Eldridge, Mark D.b.; Gonzalez, Antonio; Helgen, Kristofer M. (Zootaxa, 2017)
The taxonomic identity and status of the Australian Dingo has been unsettled and controversial since its initial description in 1792. Since that time it has been referred to by various names including Canis dingo, Canis lupus dingo, Canis familiaris and Canis familiaris dingo. Of these names C. l. dingo and C. f. dingo have been most often used, but it has recently been proposed that the Australian Dingo should be once again recognized as a full species—Canis dingo. There is an urgent need to address the instability of the names referring to the Dingo because of the consequences for management and policy. Therefore, the objective of this study was to assess the morphological, genetic, ecological and biological data to determine the taxonomic relationships of the Dingo with the aim of confirming the correct scientific name. The recent proposal for Canis dingo as the most appropriate name is not sustainable under zoological nomenclature protocols nor based on the genetic and morphological evidence. Instead we proffer the name C. familiaris for all free-ranging dogs, regardless of breed and location throughout the world, including the Australian Dingo. The suggested nomenclature also provides a framework for managing free-ranging dogs including Dingoes, under Australian legislation and policy. The broad principles of nomenclature we discuss here apply to all free-roaming dogs that coexist with their hybrids, including the New Guinea Singing Dog.